Analysis of Coastal Community Empowerment in Caring for the Environment (Case Study in the Port of Bandar Sri Setia Raja (BSSR) Selatbaru in District Bantan). (Jurnal Kajian Lingkungan, 2013)
The importance of the port as a liaison between the islands terminal carrying passengers and goods can not be denied as the presence of the Port of Bandar Sri Setia Raja (BSSR) Selatbaru in Bantan District, Bengkalis District, Riau Province. In order for this port assets can be maintained properly and make it as one of the public in obtaining alternative employment or income generation, efforts to preserve the environment around the port needs to get the attention of the people who supported of human capital (human capital), social capital (social capital) and government support.Formulation of the problem in this study is: